İdiyopatik Kronik Ürtiker Bulgurlarıyla Gelen Çölyak Hastalığı: Bir Vaka Takdimi - Dinler G.; Kalayci A.G.; Gün S. (My University, 2009)
Dinler G, Kalayci AG, Gün S. (Department of Pediatrics, Ondokuz Mayis University Faculty of Medicine, Samsun, Turkey). Celiac disease presentation as idiopathic chronic urticaria: a case report. çocuk Sağliği ve Hastaliklari Dergisi 2009; 52: 36-38. Celiac disease is an autoimmune systemic disorder induced by the intake of gluten proteins, in genetically susceptible persons. The clinical spectrum varies from classical malabsorption to asymptomatic silent form. It is known to be associated with other autoimmune diseases such as insulin-dependent diabetes mellitus and autoimmune thyroiditis. In this regard, an association of celiac disease and idiopathic chronic urticaria may be expected frequently, but there are only a few such reports in the literature. In this paper, we report a case with celiac disease who has been followed for five years as chronic urticaria.
Keywords: Celiac; Chronic Urticaria